Impaired left ventricular filling in COPD and emphysema: is it the heart or the lungs? The Multi-Ethnic Study of Atherosclerosis COPD Study - Smith, Benjamin M; Prince, Martin R; Hoffman, Eric A; Bluemke, David A; Liu, Chia-Ying; Rabinowitz, Dan; Hueper, Katja; Parikh, Megha A; Gomes, Antoinette S; Michos, Erin D; Lima, João A C; Barr, R Graham (Chest, 2013)
COPD and heart failure with preserved ejection fraction overlap clinically, and impaired left ventricular (LV) filling is commonly reported in COPD. The mechanism underlying these observations is uncertain, but may include upstream pulmonary dysfunction causing low LV preload or intrinsic LV dysfunction causing high LV preload. The objective of this study is to determine if COPD and emphysema are associated with reduced pulmonary vein dimensions suggestive of low LV preload. The population-based Multi-Ethnic Study of Atherosclerosis (MESA) COPD Study recruited smokers aged 50 to 79 years who were free of clinical cardiovascular disease. COPD was defined by spirometry. Percent emphysema was defined as regions < -910 Hounsfield units on full-lung CT scan. Ostial pulmonary vein cross-sectional area was measured by contrast-enhanced cardiac magnetic resonance and expressed as the sum of all pulmonary vein areas. Linear regression was used to adjust for age, sex, race/ethnicity, body size, and smoking. Among 165 participants, the mean (± SD) total pulmonary vein area was 558 ± 159 mm2 in patients with COPD and 623 ± 145 mm2 in control subjects. Total pulmonary vein area was smaller in patients with COPD (-57 mm2; 95% CI, -106 to -7 mm2; P = .03) and inversely associated with percent emphysema (P < .001) in fully adjusted models. Significant decrements in total pulmonary vein area were observed among participants with COPD alone, COPD with emphysema on CT scan, and emphysema without spirometrically defined COPD. Pulmonary vein dimensions were reduced in COPD and emphysema. These findings support a mechanism of upstream pulmonary causes of underfilling of the LV in COPD and in patients with emphysema on CT scan.